Case Study of Alternative Joint Property Dispute Resolution Through Mediation - Siti Arifahsyam; Mohammad Amir Bin Wan Harun (ISNU Sumatera Utara, 2024)
The resolution of joint property disputes is often a source of conflict in divorce, which requires alternative approaches such as mediation to achieve a fair and satisfactory outcome for both parties. This study uses a normative juridical approach with a case study method, examining a number of cases of joint property disputes resolved through mediation in several religious courts. The results of the study show that mediation is able to reduce tensions between the parties and speed up the dispute resolution process, compared to the litigation process. In addition, mediation offers a more flexible and customizable solution to each party's needs, which is often not achievable through the courts. The conclusion of this study is that mediation is an effective alternative in resolving joint property disputes, especially in the context of divorce. It is recommended that religious courts further promote the use of mediation and provide additional training for mediators to improve the quality of dispute resolution through this means. These findings are expected to contribute to the development of a more responsive and inclusive legal system.